2016
DOI: 10.5206/cjsotl-rcacea.2016.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Student Engagement in a Large Classroom: Using Technology to Generate a Hybridized Problem-based Learning Experience in a Large First Year Undergraduate Class

Abstract: Large first year undergraduate courses have unique challenges in the promotion of student engagement and self-directed learning due to resource constraints that prohibit small group discussions with instructors. The Monthly Virtual Mystery was developed to increase student engagement in a large (N = 725) first year undergraduate class in anthropology at the University of Toronto Mississauga. The teaching challenge was to develop a participation component (worth 6% of the final grade) that would increase studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Of the 42 A&H studies, the sub-field of languages accounts for 36 studies (83.3%) (Appendix C). English was the language most often researched (64.8%, n = 27), with six studies investigating other A&H subjects, for example anthropology (Fukuzawa & Boyd, 2016) or women's health and human rights (Carver, Davis, Kelley, Obar, & Davis, 2012). The 42 studies were published in 41 articles, as Carver et al (2012) reported on four independent studies, two of which investigated disciplines pertaining to A&H. Studies in this sample are cited 30.95 times (SD = 44.62) on average.…”
Section: Study Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Of the 42 A&H studies, the sub-field of languages accounts for 36 studies (83.3%) (Appendix C). English was the language most often researched (64.8%, n = 27), with six studies investigating other A&H subjects, for example anthropology (Fukuzawa & Boyd, 2016) or women's health and human rights (Carver, Davis, Kelley, Obar, & Davis, 2012). The 42 studies were published in 41 articles, as Carver et al (2012) reported on four independent studies, two of which investigated disciplines pertaining to A&H. Studies in this sample are cited 30.95 times (SD = 44.62) on average.…”
Section: Study Characteristicsmentioning
confidence: 96%
“…Only two studies (4.8%) provided a definition of student engagement (Fukuzawa & Boyd, 2016;Lu & Churchill, 2014). Fukuzawa and Boyd (2016, p.…”
Section: Theoretically Grounding Research On Student Engagement and Ementioning
confidence: 99%
“…These hybridized versions of PBL demonstrate its flexibility for different learning contexts but make it difficult and often futile to compare student motivation between different PBL implementations (SavinBaden, 2014). Hybridized forms of PBL can be used to introduce students to active learning because they can be modified for the context and student population (Fukuzawa & Boyd, 2016). We recommend short weekly problems in introductory PBL courses.…”
Section: Instructional Supportmentioning
confidence: 99%
“…Problem-based learning began as a teaching method to foster problem-solving skills in medical students (Barrows, 1996;Barrows & Tamblyn, 1980). It has subsequently been successful in other professional science-based programs (Masek, Yamin, & Ridzuan, 2011;Prosser, 2004;Vardi & Ciccarelli, 2008); however, the extension of PBL to the wider undergraduate curriculum has primarily involved modified (i.e., hybridized) versions that integrate mini-lectures or content driven sessions as scaffolding to accommodate larger class sizes and greater student diversity (Allen, Donham, & Bernhardt, 2011;Fukuzawa & Boyd, 2016;Savin-Baden, 2014).…”
mentioning
confidence: 99%
“…In their study Klegeris and Hurren (2011) concluded that PBL can be used successfully in large classes without any extra tutor. The advocates of PBL argue that the best way of learning is learning through active participation rather than being passive recipient of readymade information (Fukuzawa & Boyd, 2016). The steps of PBL indicates that this technique improves the students' ability for thinking ad explaining things critically which is vital in Sociology teaching in tertiary level.…”
Section: Problem Based Learning As a Technique Of Effective Teaching mentioning
confidence: 99%